The invention of curried sausage - Timm, Uwe,Vennewitz, Leila (New Directions, 1995)
To learn the origin of this popular German sidewalk food, the narrator tracks down Lena Bruckner in a retirement home in Hamburg. And, yes, it was her invention, but it's a long story, one which he cajoles from her over teas. It all started in April 1945 when she met, seduced and held captive a young deserter. The war over, the lover escaped and Lena went into business. That's where the sausage comes in
Keywords: Sausages